Mechanical reinforcement and creep resistance of coextruded wood flour/polyethylene composites by shell‐layer treatment with nano‐ and micro‐SiO2 particles. Issue 4 (1st May 2018) - Hao, Xiaolong; Zhou, Haiyang; Xie, Yanjun; Xiao, Zefang; Wang, Haigang; Wang, Qingwen
Abstract : Nano‐ and micro‐SiO2 particles (termed nSiO2 and mSiO2, respectively) were incorporated in the shell layer of a coextruded wood flour/high density polyethylene composite (WF/HDPE) to improve the mechanical properties and inhibit creep behavior. The effects of loading content, particle size, and surface treatment of the silica with vinyl trimethoxy silane (VTS) were investigated on the properties of the resulting coextruded WF/HDPE composites. Scanning electron microscopy revealed proper interfacial adhesion between the core and shell layers. nSiO2 exhibited higher reinforcement efficacy than that of mSiO2 for the shell‐layer materials. Incorporation of the VTS‐treated nSiO2 caused an increase in flexural‐ and impact strength of the coextruded composites by 29% and 57%, compared to the non‐silica filled coextruded WF/HDPE controls, respectively. Incorporation of nSiO2, either untreated or VTS‐treated, enhanced creep resistance of shell layer materials; however, only VTS‐nSiO2 worked for the coextruded composites. These findings demonstrate that filling with silica, particularly VTS‐treated nSiO2, in the shell layer substantially and economically reinforces coextruded shell/core‐structured WF/HDPE composites. POLYM. COMPOS., 40:1576–1584, 2019. © 2018 Society of Plastics Engineers